2004
DOI: 10.1111/j.1365-2672.2004.02255.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of Saccharomyces cerevisiae strains isolated from wine-producing areas in South America

Abstract: Aims:The wide use of yeast inoculum for wine fermentations permit the spreading of commercial Saccharomyces strains in wine areas all over the world. To study the impact of this practice on the autochthonous yeast populations it is necessary to have tools that permit the evaluation of the geographical origin of native isolates and differentiate them from commercial strains. Methods and Results: Electrophoretic karyotyping and mitochondrial DNA restriction analysis were used to characterize the genome of native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 26 publications
(44 reference statements)
2
36
2
Order By: Relevance
“…This assumption is at the base of the Appellation of Origin systems around the globe, with a strong impact on the wine market since they drive consumer choices. Many research groups have explored the opportunity to isolate, select and use indigenous strains with technological properties and quality traits as a strategic asset for wine-makers to unequivocally link a wine with its environment of production (Furdíkova et al, 2014;Martínez et al, 2004;Rodríguez-Palero et al, 2013;Settanni et al, 2012;Tosi et al, 2009;Tristezza et al, 2012). This experimental activity might also be interesting for the manufacturers of starter cultures, because it is the basis for genetic improvement and formulation of new products (Giudici et al, 2005;Mannazzu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is at the base of the Appellation of Origin systems around the globe, with a strong impact on the wine market since they drive consumer choices. Many research groups have explored the opportunity to isolate, select and use indigenous strains with technological properties and quality traits as a strategic asset for wine-makers to unequivocally link a wine with its environment of production (Furdíkova et al, 2014;Martínez et al, 2004;Rodríguez-Palero et al, 2013;Settanni et al, 2012;Tosi et al, 2009;Tristezza et al, 2012). This experimental activity might also be interesting for the manufacturers of starter cultures, because it is the basis for genetic improvement and formulation of new products (Giudici et al, 2005;Mannazzu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Thus in recent years, much work has been carried out on the ecology of wine yeasts, in order to ascertain the existence of strains typical of one ecosystem and also to carry out selection programmes of the yeasts representative of each wine-producing zone (Frezier and Dubordieu, 1992;Vezinhet et al, 1992;Gutierrez et al, 1999;Romano et al, 2003;Cappello et al, 2004;Martinez et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The high level of polymorphism in the structure of the nuclear and mitochondrial genomes found in different studies on natural populations has allowed the differentiation of closely related isolates 22,29,37 . Different authors 4,6,12,25 have found a greater genetic variability of the mitochondrial genome.…”
Section: Discussionmentioning
confidence: 99%
“…This may be influenced by the winemaking industry whose activity facilitates the flux of strains among remote areas 25 . However, different strains of S. cerevisiae cannot be distinguished by classical biochemical methods.…”
Section: Introductionmentioning
confidence: 99%